Preparing for the ‘ethical encounter': investigating the role and type of citizen education to encourage participation in local government - Jaroszynski, Taru (Democratic Governance and Rights Unit, 2026)
The South African Constitution envisages the South African democracy as both representative and participatory. Post-apartheid local government is designed to bring government closer to the people and create spaces for community and citizen participation. Ward committees and Integrated Development Planning Forums act as the primary spaces for community involvement in local government decision making. Cornwall calls these spaces provided by the state through legal or institutional structures ‗invited spaces'. The state regards them as its spaces where citizens or their representatives are invited. Power relations pervade these spaces and determine what knowledge is produced, which voices are heard and how much influence these voices have. The provision of invited spaces as the proper spaces' to engage the state might also act to demobilise and delegitimise spaces outside these forums. The Constitutional Court has repeatedly emphasised the importance of citizen-state interaction in what it calls ‗meaningful engagement'. Cornell argues that this is informed by the notion of ubuntu and can be conceptualised as an ethical encounter'. I argue that this notion is informed by both a recognition of another's humanity and a redistribution of resources and power so that people can live a life of dignity. This dissertation looks at the possibilities for an ‗ethical encounter'at a local government level. Much has been written on the problems and challenges of local government in its structure, its politicisation and the dynamics within these invited spaces. This is compounded by service delivery protests which are directed at the inadequacy of local government. These protests suggest that the invited spaces do not provide the options for ethical encounters. These are local invited', officialised' spaces. yet they provide the potential for what Foucault calls strategic reversibility', that is an ability to turn them around and use them as sites of resistance to the hegemonic. It is suggested that the role of civil society is to educate and empower citizens outside these spaces so that the invited spaces can be used as democratic shared' sites of participation. This entails learning what these spaces should do, what is happening in reality, and the rules of the game in these spaces, as well as examining how the local power dynamics work outside of the spaces. It is about alternative forms of knowledge being developed; about critical consciousness raising and empowerment; about holding the tension between opposition to and co-operation with the state; about enhancing agency as well as the capacity for moral responsibility on a personal and social scale; and about a new form of citizenship that is not merely oppositional but is dedicated to ubuntu. This dissertation explores how this might be fostered and argues that it is a reflective NGO that should provide an education programme. It also considers various education programs already in operation and suggests that the IDASA study circles provide a potential site for such a programme. At the same time it is noted that work must be done on both side of the equation in order to enact this ethical encounter at local government level, thus structural and capacity reforms are necessary to make government more responsive.